Control of the warranty level of ether extract, gross protein and phosphorous expressed in the label of dog and cat commercial food (Veterinary Science, 2018)
The warranty level of ether extract, gross protein and phosphorusof five dogs and three cats’ commercial food labels wereanalysed. Ether extract, gross protein and phosphorous were determinedby direct intermittent extract means of soxhlet, Kjeldahland colourimetric by reduction of sulphur-molybdate respectively.Each determination was repeated three times and the meanvalue obtained was expressed as a percentage of dry matter, thereafter,the obtained values were compared with those informedby the manufacturer. The ether extract values determined of fivedogs and two cat food was lower than those expressed in the label.The phosphorous value was lower in two dog food, and thelevel of gross protein was lower in four dogs and one cat food inrelation to the label data. Just one dog food showed values of etherextract higher than those expressed in the label. The content ofmoisture was determined by the indirect gravimetric method,desiccating the sample at 65 °C for 48 hours, and observing valuesof 46.6%, lower than those informed by the label. It concludedthat all dog food had incoherency in at least one of the parameterstudied with respect to the information presented in the manufacturerlabel. In relation to the cat food just one fulfils the valuesinformed in the manufacturer label. Finally, it was stunned thelow level of moisture found in all pet food analysed.
Keywords: ether extract; phosphorous; gross protein; balanced food